KEBIJAKAN PENGUATAN KOORDINASI ANTARA PENYIDIK DENGAN PENUNTUT UMUM DALAM MENERAPKAN RESTITUSI PERKARA KEKERASAN SEKSUAL TERHADAP ANAK - Basni, Faisyal (Lex LATA, 2024)
The implementation of coordination between Investigators and Public Prosecutors regarding restitution in cases of child victims of sexual violence is hampered by several factors, namely: first, the legal substance factor, which is according to the Government Regulation concerning the Implementation of Restitution for Children Who Are Victims of Crime (PP on Child Restitution) and the Protection Law Witnesses and Victims, Investigators and Public Prosecutors are passive, limited to only accepting applications for restitution; secondly, the legal structure factor, where the passive nature means that investigators and public prosecutors do not have an obligation to notify the victim regarding the right to restitution; and third, community factors, namely the community does not know that victims have the right to restitution. The policy in the future are : first, revise the PP on Child Restitution regarding notification to child victims to obtain the right to restitution by Investigators and Public Prosecutors as an obligation; second, the Investigator's commitment to attaching the request and amount of restitution to the case file, and the authority of the Public Prosecutor to return the case file with instructions for the Investigator to complete it with an attachment to the request and amount of restitution; and third, outreach to the public by law enforcement and related parties regarding the rights of child victims of sexual violence to restitution and procedures for applying for it.